Capital structure and firm value: An empirical study in automobile industry in China - Sun, Ke (2017)
This paper employs a new database of 51 Chinese listed companies from Shang Hai and Shen Zhen exchange during the period of 2007-2016. This study tries to find the relationship between capital structure and firm value in China’s automobile industry. This paper finds the growth rate and property ratio have a negative relationship with firm value. The firm value will increase as the firm size increases. In addition, the variable of long debt-equity ratio is significantly positively related with firm value. Although the China’s automobile industry has developed rapidly in recent years, the market structure is not perfect and mature. The experimental results show that asset-liability ratio and quick ratio have no relationship with firm value.